Nihilism in Khayyámic rubáis - Abedinifard, Mostafa (My University, 2010)
One philosophical theme often attributed to Khayyámic rubáis is nihilism, which unfortunately has not been examined in detail and according to a firm theoretical basis. This paper probes into the theme in two famous Persian collections of such rubáis: Sadeq Hedayat’s edition of Taraneh-haye Khayyám as well as Forughi and Ghani’s Rubáiyát of Omar Khayyám. For this purpose, the paper consists of an introduction as well as two main parts and a conclusion. In the introduction, the necessity of holding the theory of Khayyámic rubáis–that is, a school of rubái-composing after Omar Khayyam and not the Rubáiyát of Khayyam–is explained. In the first part of the paper, which is entirely theoretical, based on Donald Crosby’s classification of nihilisms in his book, The Specter of the Absurd, two relating types of nihilism along with some common arguments for nihilism are explicated. In the second practical part, the aforementioned definitions and assumptions are applied to the rubáis under discussion.
Keywords: nihilism; rubáis; poetry